WOMEN'S LEADERSHIP STRATEGIES IN ADVANCING THE EDUCATION SECTOR TO PREPARE EXCELLENT HUMAN RESOURCES FOR THE GOLDEN GENERATION OF INDONESIA IN 2045: A CASE STUDY AT THE MALAHAYATI TRANSPORTATION MANAGEMENT COLLEGE IN JAKARTA - Mardiana; K.P.Suharyono S.Hadiningrat; Fitry Taufiq Sahary; Boy Laksmana; Sukardi; Amrin Soamole (JIPOWER : Journal of Intellectual Power, 2025)
Women's leadership is essentially no different from men's leadership, with the two being distinguished only by leadership styles resulting from gender differences inherent from birth. In this regard, the female chairperson of the Malahayati School of Transportation Management (STMT) has achieved significant progress in line with her vision and mission. The design of this research is thematic qualitative descriptive to discover and describe the female leadership strategies implemented by Dr. Hj. Mardiana, S.Pd., M.Pd., Chair of STMT Malahayati 2022-2026, in developing and advancing the education sector. The method used in this research is ethnography, where one of the researchers is the actor. The ethnographic approach was chosen to understand a phenomenon deeply and holistically in a natural way, providing insights from the participants' perspective (emic perspective), revealing implicit behavior patterns and changes over time, and producing rich and diverse data for theory development and social problem solving. From the data collection process, which was then analyzed using thematic narrative, it was found that the leadership strategy of women in advancing the education sector at STMT Malahayati is to prioritize humanistic principles in utilizing all available potential, including man, money, material, method, machine, and marketing, with the support of digital advances. However, organizational dynamics are maintained and moderated by mutual respect, openness, and collaboration based on the pentha helix, which includes elements of government, academia, industry, society, and the media. This strategy is implemented to improve the quality of education based on Outcome Based Education (OBE) while strengthening STMT Malahayati as a campus with an impact on Indonesian nationalism.